Comment: ICT in Preschool - Hilcenko, Slavoljub (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2020)
ICT Tools are not primary, but secondary learning source for teaching abstract mathematical concepts at preschool institution. As a matter of fact, for children ICT Tools don’t have the power of immediate and practical experience or experimental work, which are the primary source of learning such contents. ICT Tools can only be used to revise knowledge after children have acquired it through direct manipulative activities and experiments, which require sensory experiences (eyes, hands). In that way children estimate volume of different liquids and their dishes firstly subjectively and then objectively.